Platelet Count and Indices in Acute Uncomplicated Malaria in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Quantitative and qualitative abnormalities of platelets are common among patients with malaria infection, and these correlate with severity. Few studies documented platelet changes in uncomplicated malaria in the endemic regions. This study aimed to describe the changes in platelet counts (PLTs) and automated platelet indices in uncomplicated malaria infection in a Nigerian population.Materials and Methods:This is a comparative cross-sectional study of 152 patients presenting with symptoms of uncomplicated malaria to the general outpatient Department of Aminu Kano Teaching Hospital, Kano, Nigeria. Malaria diagnosis was made using gold-standard microscopy of Giemsa-stained thick blood smear, while PLTs and indices (mean platelet volume [MPV], plateletcrit [PCT], platelet distribution width [PDW] and platelet-large cell ratio [P-LCR]) were determined using automated haematology analyser. Data were analysed using STATA v13 and results presented in descriptive terms.P=0.05 was considered statistically significant.Results:There were more female 8 (51.3%) than male 74 (48.7%) patients. A total of 84 patients (55.3%) were malaria positive. The prevalence of malaria-positive smears was higher in males 48 (31.6%) and among the age groups of 5–14 and 15–24 years (13.8% each). Thrombocytopenia was seen in 15 (19.7%) and 2 (2.6%) of malaria-positive and malaria-negative individuals, respectively, and the difference was statistically significant (P= 0.001). Platelet indices reveal significant differences in the MPV (P= 0.0016) and P-LCR (P= 0.0265) between malaria-positive and malaria-negative patients. Although both lower mean PLT and PCT, and higher PDW were found in malaria-positive than in malaria-negative individuals, this difference was not statistically significant (P> 0.05).Conclusion:This study showed that abnormalities in PLT and indices are more common among patients with an acute febrile illness who are malaria positive than those who are malaria negative.